Western Studies of the Quranic Narrative: from the Historical Orientation into the Literary Analysis - Munirul Ikhwan (Al-Jami'ah: Journal of Islamic Studies, 2010)
The beginnings of Western interest in the Quran can be traced back to the appearance of the first complete translation of the Quran into Latin by Robert of Ketton in the twelfth century when the Muslim and Western Christian worlds has begun a long-running confrontation. In the eighteenth century, Western scholars began to be interested in studying the history and sources of the Quran. The Quranic narrative, which has its parallels in the Judeo-Christian traditions, has been studied from the historical perspective. In this approach, everything in the Quran that can be also found in earlier scriptures, is considered as borrowed, and every story that the Quran modifies is viewed as distorted. Recent Western studies have shifted into a new arena, studying the contents and styles of the Quranic narrative by analyzing its discourse and narrativity.